Numerical Solutions of Linear Abel Integral Equations Via Boubaker Polynomials Method (Baghdad Science Journal, 2024)
In this article, a numerical method based on Boubaker polynomials (BPs) was presented to solve the Linear Abel integral (LAI) Eqs of first and second types. The matrices were used to form the (LAI) Eq  into a system of linear Eqs. To get Boubaker parameters, solve this system of Eqs using the Guess elimination method. To explain the results of this method, four examples have been provided and compared with the results of many methods mentioned in previous research. MATLAB R2018b program was used to perform all calculations and graphs.